2021
DOI: 10.1108/scm-05-2020-0198
|View full text |Cite
|
Sign up to set email alerts
|

Designing supply chain performance system: a strategic study on Indian manufacturing sector

Abstract: Purpose A well-designed supply chain performance measurement system, should account for not only the capabilities and performance attributes of the focal firm but also its supply chain partners. The purpose of this paper is to help design a system that strikes a balance between the strategic objectives of the focal firm and its supply partners vis-à-vis the requirements of supply chain performance (cost, quality, speed and customer taste). Design/methodology/approach A theoretical framework on the strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 84 publications
(96 reference statements)
0
41
0
Order By: Relevance
“…It is been observed that perceived quality affects the perceived price (Solakis et al, 2022). The cocreation can result in reduced earnings, particularly if enterprises have a greater ability to convert an investment into lower customer participation costs, which is surprising given competition (Kumar and Sharma, 2017a;Yang et al, 2021;Jha et al, 2022). Kapaj et al's (2013) conjoint choice experiment survey was constructed to finalize the customer preferences related to the milk industry in a specific market.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…It is been observed that perceived quality affects the perceived price (Solakis et al, 2022). The cocreation can result in reduced earnings, particularly if enterprises have a greater ability to convert an investment into lower customer participation costs, which is surprising given competition (Kumar and Sharma, 2017a;Yang et al, 2021;Jha et al, 2022). Kapaj et al's (2013) conjoint choice experiment survey was constructed to finalize the customer preferences related to the milk industry in a specific market.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…In the global markets, and during the last decade, most of the firms are facing many different challenges due to the rapid development of technology as the product life cycle has become shorter as well as the changing market demands ( Jha et al., 2022 ; Yang et al., 2019a , Yang et al., 2019b ). Therefore, many manufacturing firms and their several logistical activities in general, logistical transportation operations in particular, are increasingly driven by clients wants rather than forecasts ( Giannakis et al., 2019 ).…”
Section: Theoretical Background Related Literature Reviewmentioning
confidence: 99%
“…A number of firms have made many improvements that have reduced and mitigated deficiencies due to poor supplier response, unexpected customer requirements, and needs in an uncertain business environment ( Jha and Sharma, 2022 ; Feng et al., 2019 ). Therefore, the recognition and focus on the importance and role of SCR as a phenomenon have brought wide concern among corporate directors, practitioners, and scholars in conquering the business universe.…”
Section: Theoretical Background Related Literature Reviewmentioning
confidence: 99%
“…The set of operations coordinated by an organization to buy and manage supplies is referred to as the supply chain management (SCM) process (Oliver and Webber, 1982; Jha et al. , 2021; Kumar et al.…”
Section: Literature Review Regarding the Current Inquiry A Survey Of ...mentioning
confidence: 99%
“…The set of operations coordinated by an organization to buy and manage supplies is referred to as the supply chain management (SCM) process (Oliver and Webber, 1982;Jha et al, 2021;Kumar et al, 2021). The supply chain is a network of enterprises that are involved in a variety of processes and activities that result in value being produced in the form of products and services in the hands of the end consumer via upstream and downstream links (Kumar et al, 2021;Christopher, 2016).…”
Section: Supply Chain and Covid-19 Outbreakmentioning
confidence: 99%